Possibilities of Eliminating the Higher Amount of Iron in Secondary AlSi7Mg0.3 Alloy by Chrome - Bolibruchova, Dana; Richtarech, Lukas; Orlowicz, Wladyslaw (Communications - Scientific letters of the University of Zilina, 2014)
This paper deals with influence on segregation of iron based phases by chrome. Iron is one of the most common impurities that could be found in Al-Si alloys. It is impossible to remove iron from melt by standard operations, but it is possible to eliminate its negative influence by addition of some other elements that affect the segregation of intermetallics in less harmful type. Realization of experiments and results of analysis show new perspective on solubility of iron based phases during melt preparation with higher iron content and influence of chrome as iron corrector of iron based phases. It could be concluded that higher amount of chrome causes the formation of sludge particles.